Effect of precursor thermal history on the formation of amorphous and crystalline calcium carbonate - Singh, Jitendra Pal; Ji, Mi-Jung; Shim, Cheol-Hwee; Kim, Sang Ok; Chae, Keun Hwa (ELSEVIER SCIENCE INC, 2017)
The role of the thermal history of the precursor was studied for amorphous and crystalline calcium carbonate phases synthesized from calcium nitrate. The X-ray diffraction patterns of these phases are influenced by their annealing temperature of 0, 300, 400, and 500 degrees C. However, the effect of the precursor thermal history on the X-ray diffraction pattern of the resulting calcium carbonate phase is negligible. Transmission electron microscopy indicates that materials annealed at 400 degrees C consist of amorphous aggregates, irrespective of the precursor thermal history. The crystallite size of crystalline calcium carbonate is influenced by the precursor thermal history, and ranges from 23 to 26 nm. Near-edge X-ray absorption fine structure measurements indicate that the annealing temperature plays an important role in determining the local electronic structure. The role of the thermal history of the precursor is also important for the resulting electronic structure. (C) 2017 Chinese Society of Particuology and Institute of Process Engineering, Chinese Academy of Sciences. Published by Elsevier B.V. All rights reserved.
Keywords: BIOMINERALIZATION; SPECTRA; XANES; EDGE; NANOPARTICLES; PARTICLES; POLYMERS; CACO3